2015
DOI: 10.1016/j.physbeh.2015.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The role of dopamine in the pursuit of nutritional value

Abstract: Acquiring enough food to meet energy expenditure is fundamental for all organisms. Thus, mechanisms have evolved to allow foods with high nutritional value to be readily detected, consumed, and remembered. Although taste is often involved in these processes, there is a wealth of evidence supporting the existence of taste-independent nutrient sensing. In particular, post-ingestive mechanisms arising from the arrival of nutrients in the gut are able to drive food intake and behavioural conditioning. The physiolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 96 publications
(157 reference statements)
2
25
0
1
Order By: Relevance
“…The activity of the hunger hormone ghrelin and orexin modulates food- and food-cue NAc dopamine responses (Cone et al . 2014, Cone et al 2015, McCutcheon 2015), providing a potential mechanism for the need-based modulation of cue-evoked dopamine signaling detected here. It is interesting that the cue-evoked dopamine signaling was modified by satiety without the requirement to re-experience (i.e., re-taste) the predicted foods in the novel sated state.…”
Section: Discussionmentioning
confidence: 77%
“…The activity of the hunger hormone ghrelin and orexin modulates food- and food-cue NAc dopamine responses (Cone et al . 2014, Cone et al 2015, McCutcheon 2015), providing a potential mechanism for the need-based modulation of cue-evoked dopamine signaling detected here. It is interesting that the cue-evoked dopamine signaling was modified by satiety without the requirement to re-experience (i.e., re-taste) the predicted foods in the novel sated state.…”
Section: Discussionmentioning
confidence: 77%
“…Several studies using microdialysis or fast‐scan voltammetry report an increase in dopamine release in the NAc during consumption or intra‐oral injection of sweet solutions (Hajnal & Norgren, ; Bassareo et al ., ; Hajnal et al ., ; Roitman et al ., ). Interestingly, changes in dopamine levels are higher for sucrose than for non‐caloric sweet rewards in food‐deprived animals (de Araujo et al ., ; Beeler et al ., ; McCutcheon, ) and can be transferred to predictive cues (Day et al ., ), suggesting an involvement of the NAc dopamine signalling in associative and motivational processes. Conversely, the dopamine system does not seem to be involved in the hedonic treatment of food rewards.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, McCutcheon (2015) suggested that post-ingestive mechanisms occurring from nutrients in the gut could impact food consumption and behavioral conditioning. The physiological processes essential to these mechanisms are multifaceted and are thought to join in mesolimbic DA signaling to translate post-ingestive sensing of nutrients that have a reinforcement reward value.…”
Section: Discussionmentioning
confidence: 99%